Evaluation of Economic Losses of Dust phenomenon on Agricultural Sector (Case Study: Masjed Soleiman County, Khuzestan Province) - Nasim Monjezi; Abdolreza Roknedineftekhari (مخاطرات محیط طبیعی, 2021)
In this regard, the present study evaluates the economic damages of dust phenomenon on the agricultural sector of Masjed Soleiman districts and estimates the willingness to pay people to control this phenomenon. The statistical population of the study is the rural households of Masjed Soleiman city in Khuzestan province. Required data were collected through 400 questionnaires through multi-stage sampling. By determining the total sample number, the sample number of each village was determined by proportional allocation based on the population of the selected villages. Also using the Logit model, factors affecting farmers' willingness to pay for crop protection against dust were estimated using Shazam 9 software and mathematical calculations with Maple 18 software. The results showed that in the study area, the variables of age, number of employees, education and income had a positive and significant effect on the willingness of farmers to pay for crop protection against dust. The total value of the damages against dust was obtained for maintenance of agricultural crops 791448408 tomans per year for Masjed Soleiman districts.